A 39-year-old man with dyspnoea, low forced expiratory volume and a large mass of the left hemithorax - Sun, Zhi-Gang; Liu, Xiang-Yan; Wang, Zhou; Shan, Bao-Zhong; Zhang, Min; Li, Zhe (Contemporary Oncology/Współczesna Onkologia, 2013)
In patients with intrathoracic neoplasms, low forced expiratory volume (FEV1) can preclude surgical treatment. Here, we present a case of a giant solitary fibroma of the pleura (SFTP) successfully treated by surgical removal in spite of low FEV1. A 39-year-old male patient was referred to our hospital with dyspnoea and chest distress. Computed tomography (CT) showed a large mass in the left chest. Spirometry showed FEV1 1.4 L (39% of the expected value). Computed tomography scan-guided transcutaneous aspiration biopsy was performed on the patient, and microscopic examination of the specimen revealed spindle tumor cells with a background of abundant collagen. Complete surgical resection was accomplished. The tumor was large and encapsulated. It measured 28 cm  20 cm  18 cm. The definitive diagnosis obtained by histopathology after resection was benign SFTP. The patient felt no dyspnoea at discharge. Surgical treatment of SFTP should be considered even in patients with a huge tumor and with increased post-operative risk.